Fabrication of an antimicrobial active packaging and its effect on the growth of Pseudomonas and aerobic mesophilic bacteria in chicken - Higuera-Barraza, Odilia Azucena; Soto-Valdez, Herlinda; Acedo-Félix, Evelia; Peralta, Elizabeth (Vitae, 2015)
Background: One of the aims of food packaging is to protect the product from environmental factors that can cause a reduction in quality. Surface growth of microorganism is one of the leading causes of food spoilage. One option is to use antimicrobial packaging to provide an increased margin of safety and quality. Objectives: The aim of this study was evaluate the effect of active packaging with eugenol on growth of Pseudomonas and aerobic mesophilic bacteria in fresh chicken pieces. Methods: Three batches of low-density polyethylene (LDPE) film, containing 0, 9.0 and 7.7, mg g-1 eugenol (control, AAF1 and AAF2, respectively), were extruded in a pilot-plant scale blown-extrusion machine. The films with eugenol lost 42.7% and 36.8% (AAF1 and AAF2, respectively) of eugenol during processing and absorbed UV-visible light at 300-261 nm. The kinetics of eugenol release from the AAF1 into the air at 5°C and 25ºC displayed Fick’s behavior, and a diffusion coefficient of 10-8 cm2 s-1 was calculated. Results: Eugenol showed antimicrobial activity on in vitro, using paper discs with 1.74, 0.87 and 0.36 mg eugenol on 108 CFU mL-1 of Pseudomonas fluorescens in Muller-Hinton agar. Chicken thighs were wrapped in the AAF2 film, and the effects on the growth of Pseudomonas and aerobic mesophilic bacteria (AMB) were evaluated after storage for 5 d at 5°C. The AAF2 showed a moderately antimicrobial effect in reducing the growth of Pseudomonas (1.1 x 106 CFU g-1) relative to growth in the control film (6.0 x 106 CFU g-1) (P < 0.05). The film with eugenol was effective in reducing the growth of AMB (9.0 x 105 CFU g-1) relative to growth in the control film (1.7 x 106 CFU g-1) (P < 0.05). Conclusions: Despite the high losses of eugenol during the extrusion of the films, they showed an antimicrobial effect during contact with fresh chicken under commercial conditions. This study shows the potential use of eugenol for application in LDPE antimicrobial packaging film.